Antipsychotic Use and Foster Care Placement Stability Among Youth With Attention-Deficit Hyperactivity/ Disruptive Behavior Disorders. Issue 4 (7th August 2016) - Tai, Ming-Hui; Shaw, Terry; dosReis, Susan
Abstract : The objective of this study was to investigate the association between antipsychotic initiation and placement transitions among youth in foster care with attention-deficit/hyperactivity disorder and other disruptive behavior disorders (ADHD/DBD). Data were obtained from child welfare administrative records and Medicaid claims in one Mid-Atlantic state from January 1, 2010, through March 31, 2014. Cox proportional hazard model was conducted to estimate the risk of time to first placement transition during the 180-day follow-up among new antipsychotic users and propensity score matched nonusers. Results showed youth initiating antipsychotics had no significant reduction in foster placement transitions within the 180-day follow up (Hazard Ratio = 1.1; 95% CI = 0.7–1.6). Although antipsychotics are widely used for aggressive behaviors, a better understanding of clinical management of youth in foster care is needed to promote stable foster placement.